The induction of cytotoxicity, oxidative stress, and genotoxicity by root canal sealers in mammalian cells - Ribeiro Camargo, Carlos Henrique [UNESP]; Afonso Camargo, Samira Esteves; Valera, Marcia Carneiro [UNESP]; Hiller, Karl-Anton; Schmalz, Gottfried; Schweikl, Helmut (Mosby-elsevier, 2009)
Objective. Toxicologic aspects of the root canal sealers Acroseal, Epiphany, AH Plus, and castor oil polymer (COP) were analyzed using cell culture techniques.Study design. Set materials were extracted in culture medium, and cytotoxicity and the generation of reactive oxygen species (ROS) were determined in human pulp cells. The formation of micronuclei (MN), indicative of genotoxicity and changes of the cell cycle, were analyzed in V79 cells.Results. The ranking of the most to the least toxic material was: Acroseal > Epiphany = AH Plus >> COP. The production of ROS was increased by Epiphany, Acroseal, and AH Plus about 4-7-fold, but enhanced ROS production was not detected with COP. Acroseal, Epiphany, and AH Plus increased the numbers of MN, and Acroseal delayed the cell cycle in G2 phase.Conclusion. The materials which tested cytotoxic in the present study may be able to alter oral tissue-specific functions and cause inflammation. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2009; 108: 952-960)